Pulmonary Fat Embolism Syndrome After Liposuction Surgery. Issue 1 (January 2019) - Saon, Md; Walker, David; Nair, Girish B.; Al-Katib, Sayf
Abstract : Fat embolism syndrome (FES) after liposuction is very rare. Up until now, only 18 cases, including this case, of liposuction-induced FES have been reported. FES is underdiagnosed due to the lack of sensitive and specific laboratory tests and clinical findings. We present the case of a 52-year-old woman who developed FES as a complication of liposuction of the axilla, pectoris, and back. This case presents the typical radiologic findings in a patient with liposuction-induced FES. With the growing number of liposuction procedures, it is important for physicians to become aware of the fact that liposuction is not a risk-free procedure.